2020
DOI: 10.3390/ijms21124201
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Metabolic Regulation of Alternative Oxidase under Nutrient Deficiency—Interaction with Arbuscular Mycorrhizal Fungi and Rhizobium Bacteria

Abstract: The interaction of the alternative oxidase (AOX) pathway with nutrient metabolism is important for understanding how respiration modulates ATP synthesis and carbon economy in plants under nutrient deficiency. Although AOX activity reduces the energy yield of respiration, this enzymatic activity is upregulated under stress conditions to maintain the functioning of primary metabolism. The in vivo metabolic regulation of AOX activity by phosphorus (P) and nitrogen (N) and during plant symbioses with Arbuscular my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 163 publications
(239 reference statements)
1
11
0
Order By: Relevance
“…These same authors concluded that the symbiotic partners exhibited 'metabolic integration' between them, where nitrogen metabolism was 'decoupled' from photosynthesis in the photosynthetic partner in the sense that photosynthesis proceeded at high rates irrespective of nitrogen status by carbohydrate consumption by the nonphotosynthetic partner and associated relief of back-pressure into photosynthetic electron transport and prevention of excess ROS formation (Xiang et al 2020). Moreover, interaction of the plant rhizosphere microbiome with the plant's AOX was reported by Ortíz et al (2020). Fig.…”
Section: Plant Microbiome and Plant Productivitymentioning
confidence: 97%
See 1 more Smart Citation
“…These same authors concluded that the symbiotic partners exhibited 'metabolic integration' between them, where nitrogen metabolism was 'decoupled' from photosynthesis in the photosynthetic partner in the sense that photosynthesis proceeded at high rates irrespective of nitrogen status by carbohydrate consumption by the nonphotosynthetic partner and associated relief of back-pressure into photosynthetic electron transport and prevention of excess ROS formation (Xiang et al 2020). Moreover, interaction of the plant rhizosphere microbiome with the plant's AOX was reported by Ortíz et al (2020). Fig.…”
Section: Plant Microbiome and Plant Productivitymentioning
confidence: 97%
“…1, 5, and 6), including: -provision of additional sinks for carbohydrates (Stefan et al 2013, Ishizawa et al 2017, Yamakawa et al 2018; -supply of nutrients that support the growth of sink tissues without disrupting nitrogen metabolism; -production of regulators of plant metabolism and growth with an emphasis on restoration of redox homeostasis via, e.g., synthesis of plant hormones (Vacheron et al 2013) and input into central signaling networks that control photosynthetic capacity and growth. Such regulation may specifically include buffering of departures from plant redox homeostasis when environmental conditions shift (see, e.g., de Sousa Leite and Monteiro 2019, Ortíz et al 2020).…”
Section: Plant Microbiome and Plant Productivitymentioning
confidence: 99%
“…An integrative review of literature on (i) plant performance under high CO 2 and (ii) plant-microbe interaction and symbioses between photosynthetic and non-photosynthetic organisms [58] suggests that microorganisms can enhance plant photosynthetic productivity and nutritional quality (Figures 10 and 11) by (i) serving as an additional sugar sink that prevents carbohydrate build-up [130,132,[135][136][137][138] and resulting excess ROS formation (see above), (ii) balancing nutrient supply (limiting or excess; see above) and producing growth factors [139], (iii) producing gene regulators that safely re-route electrons and, thereby, further counteract disruption of redox homeostasis under both limiting nutrient supply and very high nitrate supply (see, e.g., [108,140]). Alternative outlets for electrons include cyclic electron flow in the chloroplast [141][142][143][144][145][146].…”
Section: Plant-microbe Interaction and The Abiotic Environmentmentioning
confidence: 99%
“…Plant AOX levels increased in response to high CO 2 and light supply [147,148,154] as well as under limiting nitrogen [155]. Furthermore, the plant rhizosphere microbiome interacts with plant AOX [140]. Plant-microbe interaction may thereby allow plants to take advantage of high light and CO 2 for growth and biomass accumulation by maintaining a high photosynthetic capacity with high levels of photosynthetic protein, chlorophyll, and chlorophyll-protecting antioxidants.…”
Section: Plant-microbe Interaction and The Abiotic Environmentmentioning
confidence: 99%
“…Among these, mutualistic symbiosis is characterized by reciprocal fitness advantages that often play a role in the function and development of both the hosts and the symbionts (Russell et al, 2014;Stoy et al, 2020). Across eukaryote hostmicrobe symbioses, nutrient exchange and nutritional interdependence appears pervasive (Douglas, 1998;Russell et al, 2014;Ortíz et al, 2020). Indeed, some microbial symbionts can provide essential metabolites (such as amino acids and vitamins) that the host requires but is unable to obtain without this partner (Hosokawa et al, 2010;Russell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%